The Impact of the Compensation Strategy on Organizational Loyalty "An Empirical Study of Jordanian Duty Free Shops" - AL-Qaralleh, Ghaith Bassam Mohammad (Journal of Economic, Administrative and Legal Sciences, 2019)
The main objective of this study is to identify the impact of the compensation strategy on the organizational loyalty of Jordanian free markets. In order to achieve the objective of the study, a questionnaire was developed and distributed to (70) individuals, and (60) individuals’ questionnaires with the percentage of (85.4%) were studied. They were selected in a stratified random sample using descriptive statistics and inferential statistics for analyzing the study data. The study found many significant results and the most important one was that there is a significant impact of the compensation strategy on the organizational loyalty of the Jordanian trade organizations, especially, Jordanian free markets. The study recommended conducting further research on the subject of the study as it was found that there is a lack of such research in this field.